ANALISIS FAKTOR PENENTU PELAKU USAHA MENJUAL MELALUI SITUS JUAL BELI ONLINE BUKALAPAK - Nina Fapari Arif; Asrul Nur (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2019)
The development of the internet continues to increase, with the increasing number of internet users making businessmen easier in selling their products through online, where the businessmen as the of e-commerce businessmen wants an online market place that is easy to use and can be trusted in transacting and selling through online, thus the e-commerce businessmen continues to increase supported by a lot of online trading sites that have already exist in Indonesia. Bukalapak is one of the choices for businessmen to sell and has already had a large number of sellers, that is because of the factors from the characteristics of Bukalapak itself that make the businessmen decide to sell in Bukalapak. This research aims to know the easy factor and trust factor as the determining of businessmen to sell through Bukalapak online sale site. The method used is survey technique with descriptive quantitative approach, where the data obtained from the distribution of online questionnaires by a hundred sellers in Bukalapak as respondents selected. Data analysis use tabulated data presented in the form of percentage graph then it is analyzed descriptively. The result of research show that most of the businessmen selling in Bukalapak agree that the easy factor and trust factor are determining businessmen sell through Bukalapak online sale site. Keywords: The ease of, Confidence, Businessmen, Bukalapak